The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s12560-023-09561-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis A RNA, Hepatitis E RNA, Human Adenovirus F DNA, and Norovirus RNA in Fresh and Frozen Berry Products at Point of Retail in Ireland

Abstract: Soft fruits are at particular risk of contamination with enteric viruses such as Hepatitis A virus (HAV), Hepatitis E Virus (HEV), Norovirus (NoV), Human Adenovirus (HAdV) and Sapovirus (SaV). The aim of this study was to investigate, for the first time, the presence of these biological agents in ready to eat (RTE) berries at point of retail in Ireland. A sampling strategy was designed in which RTE fresh and frozen strawberries and raspberries were purchased from five retailers between May and October 2018. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In countries with tropical and subtropical climates, HEV1 and HEV2 infection occurs mainly through contaminated water, while in countries with cold and temperate climates, the virus is suggested to spread mostly by eating raw pork or contact with pigs carrying the virus [ 4 ]. Evidence of the long-term survival of HEV on fresh and frozen strawberries has been reported [ 5 ]. Our previous studies have shown a high prevalence of HEV in Estonian domestic pigs and wild boars, which are considered the main reservoir of HEV [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In countries with tropical and subtropical climates, HEV1 and HEV2 infection occurs mainly through contaminated water, while in countries with cold and temperate climates, the virus is suggested to spread mostly by eating raw pork or contact with pigs carrying the virus [ 4 ]. Evidence of the long-term survival of HEV on fresh and frozen strawberries has been reported [ 5 ]. Our previous studies have shown a high prevalence of HEV in Estonian domestic pigs and wild boars, which are considered the main reservoir of HEV [ 6 ].…”
Section: Introductionmentioning
confidence: 99%